Corporate Social Responsibility, Corporate Financial Performance and the Confounding Effects of Economic Fluctuations - Lestari, Vivi Duwi; Soraya, Aya; Hwihanus, Hwihanus (Indonesian Journal Publisher, 2024)
This study aims to explore the relationship between Corporate Social Responsibility (CSR) and corporate financial performance in five different countries: USA, UK, Germany, Japan, and Australia. Data is obtained from studies that measure CSR through various metrics, such as CSR Index, CSR Score, CSR Disclosure, CSR Rating, and CSR Spending, while financial performance is measured using various indicators such as Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin, Tobin's Q, Operating Income, and Market Value. Data analysis was performed using linear regression statistical methods to evaluate the relationship between CSR variables and financial performance. It found that there was a significant positive relationship between CSR and corporate financial performance in all countries studied. Companies that are more active in CSR activities tend to record better financial performance. Variations between countries suggest that local context influences the strength of these relationships. The managerial implication of these findings is that investing in CSR can improve a company's reputation, strengthen its position in the market, and improve long-term financial performance. However, further studies are still needed to understand the factors influencing the relationship between CSR and financial performance across various industry and geographic contexts.